ANALISIS PENILAIAN PENGGUNA TERHADAP KUALITASLAYANAN WEBSITE YAYASAN BEASISWA JAKARTAMENGGUNAKAN METODE WEBQUAL 4.0 - Catra Butu Winardi (2021)
Website is growing very fast and rapid. Websites are used by many organizations and companies in running their business processes. Yayasan Beasiswa Jakarta uses the website to disseminate information and register for scholarships. However. on the website of Yayasan Beasiswa Jakarta. there are still many aspects that must be considered. Accordingly. it is necessary to analyze the website quality based on user assessments to find out how the quality of the Yayasan Beasiswa Jakarta website uses the variable indicators statement of the webqual 4.0 method which includes the dimensions of usability. information quality. and service interaction quality. Quantitative methods are used to collect survey data. then distribute questionnaires based on a sampling technique from a purposive random sampling population. Testing data from research results carried out by validity test, reliability test and paired t-test sample test, then performed data analysis with analyzing the gap value between the actual assessment and the assessment of user expectations. method of webqual index (WQI) is to get the website quality value and calculating value of method importance performance analysis (IPA) based on the actual assessment and the assessment of user expectations to get recommendations for indicators for the improvement of Yayasan Beasiswa Jakarta website. After analyzing the user assessment of the service quality of the Yayasan Beasiswa Jakarta website, the score is good. And still needs to be improved in every dimension used.